Strategy for Improving Sustainability and Competitiveness of MSMEs of Seafood Processed Products at Ria Kenjeran Beach Through a Blue Economy Approach - Kunhadi, Dedy; Kartika, Mira Gayatri; Deviyanti, I Gusti Ayu Sri (IJEBD (International Journal of Entrepreneurship and Business Development), 2025)
Purpose: This research aims to formulate an appropriate strategy to improve business sustainability and competitiveness of MSMEs engaged in processed marine products in the Ria Kenjeran Beach area. Through a blue economy approach, this research aims to identify measures that support the efficient utilization of marine resources in a sustainable manner without neglecting economic, social and environmental aspects. Design/methodology/approach: The approach used in this study is qualitative with the support of quantitative data as a complement. Data were collected through field observations, interviews, questionnaires, and documentation related to the potential and challenges of seafood processing in the region. SWOT analysis and an Internal-External (IE) matrix were used to formulate an appropriate strategy with blue economy principles, which emphasize efficiency, innovation and sustainability. Findings: The results showed that MSMEs in Ria Kenjeran beach have great potential in processing seafood, but still face a number of obstacles, such as limited technology, lack of market access, and low awareness of environmentally friendly practices. The blue economy approach offers solutions through the utilization of seafood waste as value-added products, development of product diversification, and collaboration with universities and government for business capacity building. Suggested strategies include Develop environmentally friendly products, Adopt simple, cost-effective technologies for waste treatment, Create derivative products from marine processing byproducts, Optimize social networks and partnerships. Paper type: Research paper